A low VOC gas volatilization high temperature resistant hot melt adhesive composite film and preparation method thereof
By adding core-shell modified particles and crosslinking structure to the hot melt adhesive to form an interpenetrating network structure, the problem of insufficient bonding strength and heat resistance of the existing hot melt adhesive to PP and PE is solved, and good bonding performance at low VOC gas volatility and high temperature is achieved.
Patent Information
- Application Number
- CN202411957892.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hot melt adhesives have insufficient bonding strength and heat resistance to PP and PE, and will produce toxic and harmful gases under high temperature conditions, which violates the VOC emission standards of automotive interior materials.
Using ethylene vinyl acetate copolymer as the matrix, core-shell modified particles are added, and the microcapsule structure formed by tourmaline and the crosslinked structure in the intermediate 3 are coated by ultramicromontmorillonite to form an interpenetrating network structure to improve bonding performance and high temperature resistance.
Low VOC gas volatility and excellent bonding performance are achieved, good bonding performance is still maintained under high temperature conditions, and the "escape" of harmful gases is suppressed through the dual effects of physical adsorption and chemical degradation, reducing the volatility of VOC gas.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hot melt adhesive composite films, and in particular, relates to a low VOC gas volatilization high temperature resistant hot melt adhesive composite film and a preparation method thereof. Background Art
[0002] Hot melt adhesive film is a film product that is easily industrialized and prepared by calendering, casting, blowing and other methods. Compared with other hot melt adhesive products, hot melt adhesive film has the following advantages: (1) Simple operation, no complicated gluing process, just lay the hot melt adhesive film and glue the joints; (2) Hot melt adhesive bonding, it only takes a few seconds or tens of seconds to complete a bonded part, which can greatly improve the process; (3) There is no pollution during the production and use of hot melt adhesive. With the rapid development of the automobile industry, automobile interior materials are constantly updated, and the types of adhesives required are increasing. The interior design of some models uses polyethylene or polypropylene hard or soft materials. These materials are difficult to bond. It is difficult to use other adhesives except hot melt adhesives for bonding. Because of this, hot melt adhesive film has been introduced into the automobile industry in large quantities for bonding and sealing between metal materials and plastics, rubber and other materials.
[0003] The traditional process is to melt-blend polyolefin materials, montmorillonite with adsorption capacity and other additives using a twin-screw, extrude granulation, and finally form a film in a film-making device. However, the hot melt adhesives currently sold on the market have very poor bonding strength and heat resistance to PP and PE. In summer, the temperature inside the car can reach 80-100°C. This type of hot melt adhesive loses its bonding ability, exposing the metal of the car to a high temperature environment, thereby losing protection for the car. In addition, since most polyolefin materials and adhesive additives used to prepare hot melt adhesive films contain ester functional groups and residual acidic impurities, toxic and harmful gases such as formaldehyde and toluene will be generated under high temperature conditions. In addition, under high temperature conditions, the toxic and harmful gases adsorbed by montmorillonite will also "escape", which does not meet the VOC emission standards related to automotive interior materials. Therefore, it is necessary to develop a hot melt adhesive composite film with low VOC gas volatility and high temperature resistance. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a method for preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film; The purpose of the present invention can be achieved through the following technical solutions: A low VOC gas volatile high temperature resistant hot melt adhesive composite film, comprising the following materials in parts by weight: 60-70 parts of ethylene vinyl acetate copolymer, 15-25 parts of core-shell modified particles, 10-15 parts of tackifier, 2-3 parts of antioxidant and 0.5-0.8 parts of ultraviolet absorber; Preparation of core-shell modified particles: Step A1: disperse ultrafine montmorillonite in toluene, add tourmaline aqueous solution after ultrasonic dispersion for 5-10 minutes, add TEOS crosslinker after continuous ultrasonic dispersion for 5 minutes, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 5-6 hours to obtain modified montmorillonite; Furthermore, the dosage ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinker and toluene is 20 g: 10-15 mL: 0.05 mL: 50 mL; the concentration of tourmaline aqueous solution is 10 mg / mL; In step A1, the ultrafine montmorillonite dispersed in toluene is the oil phase, and the tourmaline aqueous solution is the water phase. When the tourmaline aqueous solution is added to the oil phase, the ultrafine montmorillonite in the oil phase is assembled at the oil-water interface, and the interfacial tension is reduced to form oil-in-water microcapsules, thereby forming a microcapsule structure of modified ultrafine montmorillonite encapsulating tourmaline; Step A2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added into a reaction kettle, and the stirring reaction rate was controlled to be 200-300 r / min. The temperature was raised to 50-60° C. under a nitrogen atmosphere, and the mixture was stirred for reaction for 20 hours, and then vacuum evaporated, and then washed with a hydrochloric acid solution, and then filtered with sodium sulfate. Finally, the filter cake was transferred to an oven and dried to obtain an intermediate 1; Further, the usage ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF is 0.1 mol: 0.1 mol: 1-1.5 g: 50 mL; In step A2, the acyl chloride of 3,5-dinitrobenzoyl chloride and the amino group in γ-aminopropyltriethoxysilane undergo an addition reaction to graft the silane coupling agent onto the acyl chloride of p-nitrobenzoyl chloride, and the structural formula thereof is shown below:
[0005] Step A3: Mix the intermediate 1 and methanol and add them to a reactor, control the stirring reaction rate to 150-300 r / min, heat to 55-60°C, and stir for 30 minutes until the intermediate 1 is completely dissolved, then weigh sodium disulfide and add it to the reactor, stir and react for 1.5-2 hours, filter out the emulsified sulfur while hot, then mix ricinoleic acid, DCC and NHS and add them to the reactor, control the stirring reaction rate to 150-200 r / min, cool to 25-30°C, stir and react for 2-3 hours, and evaporate under reduced pressure to obtain the intermediate 2; Further, the usage ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05 mol: 15 g: 0.1 mol: 15-21 g: 5-7 g: 150 mL; In step A3, the nitro group in the intermediate 1 is reduced to an amino group under the reduction action of sodium disulfide, and then a condensation reaction is carried out under the catalytic action of the DCC-NHS system to graft an unsaturated long alkyl chain onto the intermediate 1, and its structural formula is shown below:
[0006] Step A4: difurfuryl sulfide, intermediate 2 and DMF were mixed and added to a reactor, the stirring reaction rate was controlled to be 400-500 r / min, the temperature was raised to 70-75°C, the mixture was stirred and reacted for 2 hours, and then washed with water 3-4 times, and then transferred to a 70°C oven for drying for 24 hours to obtain intermediate 3; Further, the amount ratio of difurfuryl sulfide, intermediate 2 and DMF was 0.2mol: 0.1mol: 200mL; In step A4, the conjugated diene structure in the diffuryl sulfide can react with the enophile in the intermediate 2 to form a cross-linked polymer without a catalyst; Step A5: Mix the modified montmorillonite and the ethanol solution and add them into a stirrer, control the stirring reaction rate to 800-1000 r / min, stir for 30 minutes, add the intermediate 3, continue stirring the reaction for 5-6 hours, and then dry for 24 hours to obtain the core-shell modified particles; Further, the usage ratio of modified montmorillonite, intermediate 3 and ethanol solution is 5-10 g:30 g:50 mL; the concentration of ethanol solution is 60%; In step A5, the silane coupling agent structure in the intermediate 3 is cross-linked with the modified montmorillonite and grafted onto the modified montmorillonite to form core-shell modified particles; A low VOC gas volatile high temperature resistant hot melt adhesive composite film is prepared by the following method: Step S1: Ethylene vinyl acetate copolymer, core-shell modified particles, tackifier, antioxidant and ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and water ring granulation is performed to obtain hot melt rubber particles. The hot melt rubber particles are then passed through a twin-screw extruder for casting treatment. The temperature of each zone is controlled at 180-190°C, 190-200°C, 210-220°C, 220-230°C, and 190-210°C. The applied rotation speed is 70-80r / min, the extrusion mass is 30-40kg / min, and the film is cooled, slit, and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film.
[0007] Beneficial effects of the present invention: The present invention discloses a low-VOC gas volatility high-temperature resistant hot melt adhesive composite film, which uses ethylene vinyl acetate copolymer as a matrix and is mixed with a core-shell modified particle. Compared with the existing ethylene vinyl acetate copolymer, it has lower VOC gas volatility and excellent bonding performance, and can still maintain good bonding performance under high temperature conditions; wherein the microcapsule structure formed by ultrafine montmorillonite coating tourmaline in the core-shell modified particle, the montmorillonite has a large specific surface area and can physically adsorb and enrich the harmful gases emitted from the material and the bonding aid The tourmaline in the microcapsule structure generates a strong electrostatic potential difference under the action of temperature. This electrostatic potential difference can ionize the air to generate free electrons. The free electrons are captured by oxygen to form negative oxygen ions. The generated negative oxygen ions have a degradation effect on formaldehyde and toluene, decomposing them into odorless and non-toxic carbon dioxide and water. Through the dual effects of physical adsorption and chemical degradation, the harmful gases adsorbed by montmorillonite can be further degraded even under high temperature conditions, thereby inhibiting the "escape" of harmful gases under high temperature conditions and further reducing the volatilization of VOC gases. At the same time, the flexible long alkyl chains in the intermediate 3 grafted on the surface of the core-shell modified particles can be entangled with the ethylene vinyl acetate copolymer to form an interpenetrating network structure. On the one hand, the dispersibility of the modified montmorillonite in the ethylene vinyl acetate copolymer is improved, and its adsorption and degradation effects are further improved. On the other hand, the interpenetrating network structure can improve the high temperature resistance of the matrix and improve its bonding strength at high temperatures; and the cross-linking structure in the intermediate 3 can undergo self-cross-linking at low temperatures without a catalyst, further strengthening the initial bonding strength of the matrix. As the temperature inside the car continues to rise, the formed cross-linking structure will absorb energy first and be destroyed, reducing the influence of high temperature on the bonding performance of the matrix, and strengthening the high temperature resistance of the matrix. After being destroyed at high temperature, the cross-linking structure can be formed again when the temperature of the matrix drops, reflecting the self-healing property. DETAILED DESCRIPTION
[0008] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0009] The raw material formulas used in this embodiment and comparative example are shown in Table 1: Example 1
[0010] The specific implementation process of preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this embodiment is as follows: Preparation of core-shell modified particles a1: Disperse ultrafine montmorillonite in toluene, add a 10 mg / mL tourmaline aqueous solution after ultrasonic dispersion for 5 minutes, add TEOS crosslinker after ultrasonic dispersion for 5 minutes, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 5 hours to obtain modified montmorillonite; in the above reaction, the amount ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinker and toluene is 20g:10mL:0.05mL:50mL; a2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 200 r / min, the temperature was raised to 50°C under a nitrogen atmosphere, the mixture was stirred for reaction for 20 hours, and then vacuum evaporated, then washed with hydrochloric acid solution, filtered with sodium sulfate, and finally the filter cake was transferred to an oven for drying to obtain intermediate 1; in the above reaction, the amount ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF was 0.1 mol: 0.1 mol: 1 g: 50 mL; a3: Mix the intermediate 1 and methanol and add them to the reactor, control the stirring reaction rate to 150r / min, heat to 55°C, keep warm and stir for 30min, until the intermediate 1 is completely dissolved, then weigh sodium disulfide and add it to the reactor, keep warm and stir for 1.5h, filter out the emulsified sulfur while hot, then mix ricinoleic acid, DCC and NHS and add them to the reactor, control the stirring reaction rate to 150 / min, cool to 25°C, keep warm and stir for 2h, and evaporate under reduced pressure to obtain the intermediate 2; in the above reaction, the amount ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05mol:15g:0.1mol:15g:5g:150mL; a4: Take difurfuryl sulfide, intermediate 2 and DMF and mix them into a reactor, control the stirring reaction rate to 400r / min, heat to 70°C, keep stirring and react for 2h, wash with water 3-4 times, transfer to an oven at 70°C and dry for 24h to obtain intermediate 3; in the above reaction, the amount ratio of difurfuryl sulfide, intermediate 2 and DMF is 0.2mol:0.1mol:200mL; a5: Modified montmorillonite and 60% ethanol solution were mixed and added into a stirrer, and the stirring reaction rate was controlled to be 800r / min. After stirring for 30min, intermediate 3 was added, and then the stirring reaction was continued for 5h and dried for 24h to obtain core-shell modified particles; in the above reaction; the amount ratio of modified montmorillonite, intermediate 3 and ethanol solution was 5g:30g:50mL; Preparation of low VOC gas volatile high temperature resistant hot melt adhesive composite film s1: 60 parts of ethylene vinyl acetate copolymer, 15 parts of core-shell modified particles, 10 parts of tackifier, 2 parts of antioxidant and 0.5 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and subjected to water ring granulation treatment to obtain hot-melt rubber particles. The hot-melt rubber particles are then cast through a twin-screw extruder. The temperature of each zone is controlled at 180°C, 190°C, 210°C, 220°C and 190°C. The rotation speed is 70r / min, the extrusion mass is 30kg / min, and the film is cooled, slit and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film. Example 2
[0011] The specific implementation process of preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this embodiment is as follows: Preparation of core-shell modified particles a1: Disperse ultrafine montmorillonite in toluene, add a 10 mg / mL tourmaline aqueous solution after ultrasonic treatment for 10 minutes, continue ultrasonic dispersion for 5 minutes, add TEOS crosslinker, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 6 hours to obtain modified montmorillonite; in the above reaction, the amount ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinker and toluene is 20g:11mL:0.05mL:50mL; a2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 200 r / min, the temperature was raised to 55°C under a nitrogen atmosphere, the mixture was stirred for reaction for 20 hours, and then vacuum evaporated, then washed with hydrochloric acid solution, filtered with sodium sulfate, and finally the filter cake was transferred to an oven and dried to obtain intermediate 1; in the above reaction, the amount ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF was 0.1 mol: 0.1 mol: 1.1 g: 50 mL; a3: Mix the intermediate 1 and methanol and feed them into the reactor, control the stirring reaction rate to 200r / min, heat to 56°C, keep warm and stir for 30min, until the intermediate 1 is completely dissolved, then weigh sodium disulfide and add it to the reactor, keep warm and stir for 2h, filter out the emulsified sulfur while hot, then mix ricinoleic acid, DCC and NHS and feed them into the reactor, control the stirring reaction rate to 160 / min, cool to 26°C, keep warm and stir for 2h, and evaporate under reduced pressure to obtain the intermediate 2; in the above reaction, the amount ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05mol:15g:0.1mol:16g:6g:150mL; a4: Take difurfuryl sulfide, intermediate 2 and DMF and mix them into a reactor, control the stirring reaction rate to 450r / min, heat to 75°C, keep stirring and react for 2h, wash with water 3-4 times, transfer to an oven at 70°C and dry for 24h to obtain intermediate 3; in the above reaction, the amount ratio of difurfuryl sulfide, intermediate 2 and DMF is 0.2mol:0.1mol:200mL; a5: Modified montmorillonite and 60% ethanol solution were mixed and added into a stirrer, and the stirring reaction rate was controlled to be 850r / min. After stirring for 30min, intermediate 3 was added, and then the stirring reaction was continued for 6h and dried for 24h to obtain core-shell modified particles; in the above reaction; the amount ratio of modified montmorillonite, intermediate 3 and ethanol solution was 6g:30g:50mL; Preparation of low VOC gas volatile high temperature resistant hot melt adhesive composite film s1: 62 parts of ethylene vinyl acetate copolymer, 17 parts of core-shell modified particles, 11 parts of tackifier, 3 parts of antioxidant and 0.6 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and subjected to water ring granulation treatment to obtain hot melt rubber particles. The hot melt rubber particles are then cast through a twin-screw extruder. The temperature of each zone is controlled at 185°C, 195°C, 215°C, 225°C and 200°C. The applied rotation speed is 80r / min, the extrusion mass is 40kg / min, and the film is cooled, slit and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film. Example 3
[0012] The specific implementation process of preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this embodiment is as follows: Preparation of core-shell modified particles a1: Disperse ultrafine montmorillonite in toluene, add a 10 mg / mL tourmaline aqueous solution after ultrasonic treatment for 10 minutes, continue ultrasonic dispersion for 5 minutes, add TEOS crosslinker, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 6 hours to obtain modified montmorillonite; in the above reaction, the amount ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinker and toluene is 20g:12mL:0.05mL:50mL; a2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 250 r / min, the temperature was raised to 60°C under a nitrogen atmosphere, the reaction was stirred for 20 hours, and then the mixture was evaporated under reduced pressure, then washed with a hydrochloric acid solution, filtered with sodium sulfate, and finally the filter cake was transferred to an oven and dried to obtain an intermediate 1; in the above reaction, the amount ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF was 0.1 mol: 0.1 mol: 1.2 g: 50 mL; a3: Mix the intermediate 1 and methanol and add them to the reactor, control the stirring reaction rate to 250r / min, heat to 57°C, keep warm and stir for 30min, until the intermediate 1 is completely dissolved, then weigh sodium disulfide and add it to the reactor, keep warm and stir for 2h, filter out the emulsified sulfur while hot, then mix ricinoleic acid, DCC and NHS and add them to the reactor, control the stirring reaction rate to 170 / min, cool to 27°C, keep warm and stir for 2h, and evaporate under reduced pressure to obtain the intermediate 2; in the above reaction, the amount ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05mol:15g:0.1mol:17g:7g:150mL; a4: Take difurfuryl sulfide, intermediate 2 and DMF and mix them into a reactor, control the stirring reaction rate to 450r / min, heat to 75°C, keep stirring and react for 2h, wash with water 3-4 times, transfer to an oven at 70°C and dry for 24h to obtain intermediate 3; in the above reaction, the amount ratio of difurfuryl sulfide, intermediate 2 and DMF is 0.2mol:0.1mol:200mL; a1: Modified montmorillonite and 60% ethanol solution were mixed and added into a stirrer, and the stirring reaction rate was controlled to be 900r / min. After stirring for 30min, intermediate 3 was added, and then the stirring reaction was continued for 6h and dried for 24h to obtain core-shell modified particles; in the above reaction; the amount ratio of modified montmorillonite, intermediate 3 and ethanol solution was 7g:30g:50mL; Preparation of low VOC gas volatile high temperature resistant hot melt adhesive composite film s1: 64 parts of ethylene vinyl acetate copolymer, 19 parts of core-shell modified particles, 12 parts of tackifier, 3 parts of antioxidant and 0.7 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and subjected to water ring granulation treatment to obtain hot-melt rubber particles. The hot-melt rubber particles are then cast through a twin-screw extruder. The temperature of each zone is controlled at 190°C, 200°C, 220°C, 230°C and 210°C. The rotation speed is 80r / min, the extrusion mass is 40kg / min, and the film is cooled, slit and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film. Example 4
[0013] The specific implementation process of preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this embodiment is as follows: Preparation of core-shell modified particles a1: Disperse ultrafine montmorillonite in toluene, add a 10 mg / mL tourmaline aqueous solution after ultrasonic treatment for 10 minutes, continue ultrasonic dispersion for 5 minutes, add TEOS crosslinker, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 6 hours to obtain modified montmorillonite; in the above reaction, the amount ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinker and toluene is 20g:13mL:0.05mL:50mL; a2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 300 r / min, the temperature was raised to 60°C under a nitrogen atmosphere, the reaction was stirred for 20 hours, and then the mixture was evaporated under reduced pressure, then washed with a hydrochloric acid solution, and then filtered with sodium sulfate. Finally, the filter cake was transferred to an oven and dried to obtain an intermediate 1; in the above reaction, the amount ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF was 0.1 mol: 0.1 mol: 1.3 g: 50 mL; a3: Mix the intermediate 1 and methanol and feed them into the reactor, control the stirring reaction rate to 300r / min, heat to 59°C, keep warm and stir for 30min, until the intermediate 1 is completely dissolved, then weigh sodium disulfide and add it to the reactor, keep warm and stir for 2h, filter out the emulsified sulfur while hot, then mix ricinoleic acid, DCC and NHS and feed them into the reactor, control the stirring reaction rate to 170 / min, cool to 27°C, keep warm and stir for 2h, and evaporate under reduced pressure to obtain the intermediate 2; in the above reaction, the amount ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05mol:15g:0.1mol:19g:8g:150mL; a4: Take difurfuryl sulfide, intermediate 2 and DMF and mix them into a reactor, control the stirring reaction rate to 450r / min, heat to 75°C, keep stirring and react for 2h, wash with water 3-4 times, transfer to an oven at 70°C and dry for 24h to obtain intermediate 3; in the above reaction, the amount ratio of difurfuryl sulfide, intermediate 2 and DMF is 0.2mol:0.1mol:200mL; a5: Modified montmorillonite and 60% ethanol solution were mixed and added into a stirrer, and the stirring reaction rate was controlled to be 1000r / min. After stirring for 30min, intermediate 3 was added, and then the stirring reaction was continued for 6h and dried for 24h to obtain core-shell modified particles; in the above reaction; the amount ratio of modified montmorillonite, intermediate 3 and ethanol solution was 8g:30g:50mL; Preparation of low VOC gas volatile high temperature resistant hot melt adhesive composite film s1: 66 parts of ethylene vinyl acetate copolymer, 21 parts of core-shell modified particles, 13 parts of tackifier, 3 parts of antioxidant and 0.8 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and subjected to water ring granulation treatment to obtain hot-melt rubber particles. The hot-melt rubber particles are then cast through a twin-screw extruder. The temperature of each zone is controlled at 190°C, 200°C, 220°C, 230°C and 210°C. The rotation speed is 80r / min, the extrusion mass is 40kg / min, and the film is cooled, slit and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film. Example 5
[0014] The specific implementation process of preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this embodiment is as follows: Preparation of core-shell modified particles a1: Dissolve ultrafine montmorillonite in toluene, add a 10 mg / mL tourmaline aqueous solution after ultrasonic dispersion for 10 minutes, add TEOS crosslinker after ultrasonic dispersion for 5 minutes, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 6 hours to obtain modified montmorillonite; in the above reaction, the amount ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinker and toluene is 20g:14mL:0.05mL:50mL; a2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 300 r / min, the temperature was raised to 60°C under a nitrogen atmosphere, the mixture was stirred for reaction for 20 hours, and then vacuum evaporated, then washed with hydrochloric acid solution, filtered with sodium sulfate, and finally the filter cake was transferred to an oven and dried to obtain intermediate 1; in the above reaction, the amount ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF was 0.1 mol: 0.1 mol: 1.4 g: 50 mL; a3: Mix the intermediate 1 and methanol and feed them into the reactor, control the stirring reaction rate to 300r / min, heat to 60℃, keep warm and stir for 30min, until the intermediate 1 is completely dissolved, then weigh sodium disulfide and add it into the reactor, keep warm and stir for 2h, filter out the emulsified sulfur while hot, then mix ricinoleic acid, DCC and NHS and feed them into the reactor, control the stirring reaction rate to 190 / min, cool to 28℃, keep warm and stir for 2h, and evaporate under reduced pressure to obtain the intermediate 2; in the above reaction, the amount ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05mol:15g:0.1mol:21g:8g:150mL; a4: Take difurfuryl sulfide, intermediate 2 and DMF and mix them into a reactor, control the stirring reaction rate to 450r / min, heat to 75°C, keep stirring and react for 2h, wash with water 3-4 times, transfer to an oven at 70°C and dry for 24h to obtain intermediate 3; in the above reaction, the amount ratio of difurfuryl sulfide, intermediate 2 and DMF is 0.2mol:0.1mol:200mL; a5: Modified montmorillonite and 60% ethanol solution were mixed and added into a stirrer, and the stirring reaction rate was controlled to be 1000r / min. After stirring for 30min, intermediate 3 was added, and then the stirring reaction was continued for 6h and dried for 24h to obtain core-shell modified particles; in the above reaction; the amount ratio of modified montmorillonite, intermediate 3 and ethanol solution was 9g:30g:50mL; Preparation of low VOC gas volatile high temperature resistant hot melt adhesive composite film s1: 68 parts of ethylene vinyl acetate copolymer, 23 parts of core-shell modified particles, 13 parts of tackifier, 3 parts of antioxidant and 0.8 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and subjected to water ring granulation treatment to obtain hot-melt rubber particles. The hot-melt rubber particles are then cast through a twin-screw extruder. The temperature of each zone is controlled at 190°C, 200°C, 220°C, 230°C and 210°C. The rotation speed is 80r / min, the extrusion mass is 40kg / min, and the film is cooled, slit and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film. Example 6
[0015] The specific implementation process of preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this embodiment is as follows: Preparation of core-shell modified particles a1: Disperse ultrafine montmorillonite in toluene, add a 10 mg / mL tourmaline aqueous solution after ultrasonic treatment for 10 minutes, continue ultrasonic dispersion for 5 minutes, add TEOS crosslinker, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 6 hours to obtain modified montmorillonite; in the above reaction, the amount ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinker and toluene is 20g:15mL:0.05mL:50mL; a2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added into a reactor, the stirring reaction rate was controlled to be 300 r / min, the temperature was raised to 60°C under a nitrogen atmosphere, the mixture was stirred for reaction for 20 hours, and then vacuum evaporated, then washed with hydrochloric acid solution, filtered with sodium sulfate, and finally the filter cake was transferred to an oven for drying to obtain intermediate 1; in the above reaction, the amount ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF was 0.1 mol: 0.1 mol: 1.5 g: 50 mL; a3: Mix the intermediate 1 and methanol and feed them into the reactor, control the stirring reaction rate to 300r / min, heat to 60℃, keep warm and stir for 30min, until the intermediate 1 is completely dissolved, then weigh sodium disulfide and add it into the reactor, keep warm and stir for 2h, filter out the emulsified sulfur while hot, then mix ricinoleic acid, DCC and NHS and feed them into the reactor, control the stirring reaction rate to 200 / min, cool to 30℃, keep warm and stir for 2h, and evaporate under reduced pressure to obtain the intermediate 2; in the above reaction, the amount ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05mol:15g:0.1mol:21g:8g:150mL; a4: Take difurfuryl sulfide, intermediate 2 and DMF and mix them into a reactor, control the stirring reaction rate to 450r / min, heat to 75°C, keep stirring and react for 2h, wash with water 3-4 times, transfer to an oven at 70°C and dry for 24h to obtain intermediate 3; in the above reaction, the amount ratio of difurfuryl sulfide, intermediate 2 and DMF is 0.2mol:0.1mol:200mL; a5: Modified montmorillonite and 60% ethanol solution were mixed and added into a stirrer, and the stirring reaction rate was controlled to be 1000r / min. After stirring for 30min, intermediate 3 was added, and then the stirring reaction was continued for 6h and dried for 24h to obtain core-shell modified particles; in the above reaction; the amount ratio of modified montmorillonite, intermediate 3 and ethanol solution was 10g:30g:50mL; Preparation of low VOC gas volatile high temperature resistant hot melt adhesive composite film s1: 70 parts of ethylene vinyl acetate copolymer, 25 parts of core-shell modified particles, 15 parts of tackifier, 3 parts of antioxidant and 0.8 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and subjected to water ring granulation treatment to obtain hot-melt rubber particles. The hot-melt rubber particles are then cast through a twin-screw extruder. The temperature of each zone is controlled at 190°C, 200°C, 220°C, 230°C and 210°C. The rotation speed is 80r / min, the extrusion mass is 40kg / min, and the film is cooled, slit and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film.
[0016] Comparative Example 1 The specific implementation process of preparing the low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this comparative example is as follows: s1: 70 parts of ethylene vinyl acetate copolymer, 10 parts of montmorillonite (the modified montmorillonite in Example 5 is used as the comparative example), 10 parts of unsaturated polyester (the unsaturated long-chain polyester in CN110157005A is used in this comparative example), 3 parts of antioxidant and 0.8 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and water ring granulation is performed to obtain hot melt rubber particles. The hot melt rubber particles are then cast through a twin-screw extruder. The temperature of each zone is controlled at 190°C, 200°C, 220°C, 230°C, and 210°C. The applied rotation speed is 80r / min, the extrusion mass is 40kg / min, and the film is cooled, slit, and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film.
[0017] Comparative Example 2 The specific implementation process of preparing the low VOC gas volatilization high temperature resistant hot melt adhesive composite film in this comparative example is as follows: s1: Mix the ultrafine montmorillonite and 60% ethanol solution into a stirrer, control the stirring rate to 800r / min, stir for 10min, add KH-550, and continue stirring for 5h to obtain modified montmorillonite; in the above reaction, the dosage ratio of ultrafine montmorillonite, KH-550 and ethanol solution is 10g:0.2g:5mL; s2: 70 parts of ethylene vinyl acetate copolymer, 8 parts of modified montmorillonite, 2 parts of tourmaline, 10 parts of unsaturated polyester (intermediate 3 in Example 5 is selected in this comparative example), 3 parts of antioxidant and 0.8 parts of ultraviolet absorber are mixed and fed into a kneader for internal mixing. After kneading, the material is discharged and subjected to water ring granulation treatment to obtain hot-melt rubber particles. The hot-melt rubber particles are then passed through a twin-screw extruder for casting treatment. The temperature of each zone is controlled at 190°C, 200°C, 220°C, 230°C and 210°C, the applied rotation speed is 80r / min, the extrusion mass is 40kg / min, and the film is cooled, slit and rolled to form a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film.
[0018] Comparative Example 3 This comparative example uses the hot melt adhesive composition in CN114410246B; The low VOC gas volatilization high temperature resistant hot melt adhesive composite film prepared in Example 1-6 and the hot melt adhesive composite film of Comparative Example 1-3 were subjected to bonding strength test and formaldehyde and acetaldehyde content test according to GB / T2790-1995 and Japanese standard NESM0402; High temperature resistance test: A low VOC gas volatilization high temperature resistant hot melt adhesive composite film prepared in Example 1-6 and the hot melt adhesive of Comparative Example 1-3 were applied to the surface of a copper plate to prepare a colloid sample of a certain thickness, and hot pressed at 120°C for 2 minutes with contact pressure, and then the sample was placed vertically in an aging oven at 80°C for 3000 hours, and then the bonding strength test was performed according to GB / T2790-1995; Self-healing test: The prepared adhesive sample was placed vertically in a 130°C high temperature aging oven, baked for 10 hours and then cooled to room temperature, and then the bonding strength test was carried out in accordance with GB / T2790-1995; the specific test is shown in Table 2: Table 2
[0019] It can be seen from the data in Table 1 that the formaldehyde and toluene release amounts of a low VOC gas volatilization high temperature resistant hot melt adhesive composite film prepared in Example 1-6 are 81-89ppm and 83-92ppm. It is slightly better than the hot melt adhesive composite film in Comparative Example 1, but significantly higher than the hot melt adhesive composite film prepared in Comparative Examples 2-3; it shows that the hot melt adhesive composite film prepared in this embodiment has lower VOC volatilization, and the bonding strength at room temperature is 102-113N / 25mm, and the bonding strength at high temperature is 97-105N / 25mm, which is slightly better than the hot melt adhesive composite film in Comparative Example 2, but significantly better than the bonding strength at room temperature and high temperature bonding strength in Comparative Examples 1 and 3, indicating that the hot melt adhesive composite film prepared in this embodiment still has good bonding strength at high temperature, and under high temperature baking at 130°C, the self-healing bonding strength retention rate of this embodiment is about 85%, while the bonding strength retention rate of the hot melt adhesive composite film prepared in Comparative Examples 1-3 is less than 45%, indicating that the low VOC gas volatilization high temperature resistant hot melt adhesive composite film prepared in this embodiment has excellent self-healing properties.
[0020] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0021] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A low VOC gas volatile high temperature resistant hot melt adhesive composite film, characterized in that: The agent comprises 60-70 parts of ethylene vinyl acetate copolymer, 15-25 parts of core-shell modified particles, 10-15 parts of tackifier, 2-3 parts of antioxidant and 0.5-0.8 parts of ultraviolet absorber according to weight parts; The core-shell modified particles were prepared by the following method: Step A1: disperse ultrafine montmorillonite in toluene, add tourmaline aqueous solution after ultrasonic treatment, continue ultrasonic dispersion for 5 minutes, add TEOS crosslinker, crosslink for 48 hours, wash with anhydrous ethanol for 3 times, transfer to an oven and dry for 5-6 hours to obtain modified montmorillonite; Step A2: 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF were mixed and added, and the mixture was heated to 50-60° C. under a nitrogen atmosphere, and the mixture was stirred for reaction for 20 h, and then vacuum evaporated, and then washed with a hydrochloric acid solution, and then filtered with sodium sulfate. Finally, the filter cake was transferred to an oven and dried to obtain an intermediate 1; Step A3: Mix the intermediate 1 and methanol, heat to 55-60°C, and stir for 30 minutes until the intermediate 1 is completely dissolved. Then weigh sodium disulfide and add it to the reactor. After stirring for 1.5-2 hours, filter out the emulsified sulfur while hot. Then, mix ricinoleic acid, DCC and NHS, cool to 25-30°C, stir for 2-3 hours, and evaporate under reduced pressure to obtain the intermediate 2. Step A4: difurfuryl sulfide, intermediate 2 and DMF were mixed and added, the temperature was raised to 70-75°C, the mixture was stirred and reacted for 2 hours, washed with water 3-4 times, and then transferred to an oven and dried for 24 hours to obtain intermediate 3; Step A5: The modified montmorillonite and ethanol solution were mixed and added, and the intermediate 3 was added after stirring for 30 minutes. The reaction was continued with stirring for 5-6 hours, and then dried for 24 hours to obtain core-shell modified particles.
2. The low VOC gas volatile high temperature resistant hot melt adhesive composite film according to claim 1, characterized in that: In step A1, the usage ratio of ultrafine montmorillonite, tourmaline aqueous solution, TEOS crosslinking agent and toluene is 20g:10-15mL:0.05mL:50mL; the concentration of tourmaline aqueous solution is 10mg / mL.
3. The low VOC gas volatile high temperature resistant hot melt adhesive composite film according to claim 2, characterized in that: In step A2, the usage ratio of 3,5-dinitrobenzoyl chloride, γ-aminopropyltriethoxysilane, triethylamine and THF is 0.1 mol: 0.1 mol: 1-1.5 g: 50 mL.
4. The low VOC gas volatile high temperature resistant hot melt adhesive composite film according to claim 3, characterized in that: In step A3, the usage ratio of intermediate 1, sodium disulfide, ricinoleic acid, DCC, NHS and methanol is 0.05 mol: 15 g: 0.1 mol: 15-21 g: 5-7 g: 150 mL.
5. The low VOC gas volatile high temperature resistant hot melt adhesive composite film according to claim 4, characterized in that: In step A4, the usage ratio of difurfuryl sulfide, intermediate 2 and DMF is 0.2 mol:0.1 mol:200 mL.
6. The low VOC gas volatile high temperature resistant hot melt adhesive composite film according to claim 5, characterized in that: In step A5, the usage ratio of modified montmorillonite, intermediate 3 and ethanol solution is 5-10 g:30 g:50 mL.
7. The method for preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film according to claim 6, characterized in that: Prepared by the following method: Ethylene vinyl acetate copolymer, core-shell modified particles, tackifier, antioxidant and ultraviolet absorber are mixed and processed, then discharged and subjected to water ring granulation treatment to obtain hot melt adhesive particles, and finally the hot melt adhesive particles are cast through a twin-screw extruder to prepare a low VOC gas volatilization and high temperature resistant hot melt adhesive composite film.
8. The method for preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film according to claim 7, characterized in that: The antioxidant is antioxidant 1010.
9. The method for preparing a low VOC gas volatilization high temperature resistant hot melt adhesive composite film according to claim 7, characterized in that: The ultraviolet absorber is UV-328.
Citation Information
Patent Citations
Biological base supermolecule polyester with unsaturated long-chain alkyl and synthesis of biological base supermolecule polyester
CN110157005A